ANALISIS ASESMEN/PENILAIAN PORTOFOLIO BERBASIS TIK PADA MATA PELAJARAN IPA KELAS IV MI/SD - isti, istiqamah (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to describe the assessment / assessment of ICT-based portfolios in science subjects grade IV MI / SD. One of the benefits of using information and communication technology (ICT) in education is the ease in documenting authentic assessments as guided in the 2013 curriculum.In manual portfolio assessments there are tasks that must be assessed and observed in practical results, namely submitting work in the form of objects. real, such as printed text, handwritten text or other works. In this study, an online portfolio was introduced to be used as a media for assessment / assessment of science subjects. Online portfolios are used as a medium to accommodate all student work, both work at the request of the teacher and work on his own initiative. Teacher communication with students and students with other students can be done through social media such as Facebook, WhatsApp and other communication facilities. The method in this research is library research (library research) and by using the method of descriptive analysis. Sources of data in this study are scientific works such as journals, theses, and books that are in line with the research title. who use the publish or perish application by entering ICT-based assessment keywords and online portfolios taken from 2010-2020 which can be accessed in full text in pdf format. Data collection techniques with documentation, identifying discourse from books, articles, journals, theses, the web (internet), or other information related to authentic assessments and online portfolios. The research results obtained show that online portfolios can be applied well and as an assessment that is highly recommended to be used as a supporting tool so that the assessment / assessment in MI / SD is more optimal.